2007
DOI: 10.1186/1744-9081-3-35
|View full text |Cite
|
Sign up to set email alerts
|

1Controlled evaluation of a neurofeedback training of slow cortical potentials in children with Attention Deficit/Hyperactivity Disorder (ADHD)

Abstract: BackgroundAlthough several promising studies on neurofeedback training in Attention Deficit/Hyperactivity Disorder (ADHD) have been performed in recent years, the specificity of positive treatment effects continues to be challenged.MethodsTo evaluate the specificity of a neurofeedback training of slow cortical potentials, a twofold strategy was pursued: First, the efficacy of neurofeedback training was compared to a group training program for children with ADHD. Secondly, the extent of improvements observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
171
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(192 citation statements)
references
References 34 publications
12
171
2
4
Order By: Relevance
“…Evidence from Ref. 57 points in a similar direction. Although only half the children in their neurofeedback condition learned to regulate cortical activation during a transfer condition (without direct feedback), the neurofeedback training performance of these good performers was closely related to clinical improvement in hyperactivity (r 5 0.81) and impulsivity (r 5 0.75).…”
Section: Relation Between Training Performance and Clinical Improvementmentioning
confidence: 71%
“…Evidence from Ref. 57 points in a similar direction. Although only half the children in their neurofeedback condition learned to regulate cortical activation during a transfer condition (without direct feedback), the neurofeedback training performance of these good performers was closely related to clinical improvement in hyperactivity (r 5 0.81) and impulsivity (r 5 0.75).…”
Section: Relation Between Training Performance and Clinical Improvementmentioning
confidence: 71%
“…After the last rtfMRI‐NF run, a 5‐minute fMRI transfer run was conducted, which was identical to the NF training runs, using the same stimuli, but without the feedback (the rocket did not move), consisting of four rest and three activation blocks. Transfer runs measure retention of learning and are considered a proximal measure of successful transfer of training strategies to everyday life [Drechsler et al, 2007]. …”
Section: Methodsmentioning
confidence: 99%
“…Almost unequivocally, uncontrolled within subjects' pre-to post-treatment analyses indicate positive results with medium-to-large effect sizes (ES) [16,18,21,35,[38][39][40][41][42][43][44][45][46][47].…”
Section: Brain Electric Activity and Its Relation To Brain Functionmentioning
confidence: 99%
“…None of these studies found NF to be inferior to medication, but comparison was restricted to neuropsychological measurements in 2 of them. Drechsler et al [45] compared NF to cognitive behavioral therapy and found NF to be superior to psychotherapy according to parents and teachers ratings for inattention and metacognition, but not according to objective neuropsychological measurements. The 3 studies comparing NF to computerized attention skills training (CAST) yielded conflicting results.…”
Section: Brain Electric Activity and Its Relation To Brain Functionmentioning
confidence: 99%
See 1 more Smart Citation